1885 Mo. Laws 140 - (:unkn) unknown (My University, 1885)
An Act to amend an act entitled "an act to amend section 1274, article 2, chapter 24 of the revised statutes of Missouri, entitled 'of crimes and criminal procedure,'" § 1: Prohibited the concealed carry of any deadly or dangerous weapon into any church, or place where people have assembled for religious worship, or into any school room or place where people are assembled for educational, literary, or social purposes, or to any election precinct on any election day, or into any court room during the sitting of court, or into any other public assemblage for militia lawful purposes. Prohibited weapons include any firearm, Bowie-knife, dirk, dagger, slung-shot, or other deadly weapon.
Keywords: CARRY - CERTAIN PUBLIC PLACES